Nitrogen Competition between Corn and Weeds in Soils under Organic and Conventional Management. Issue 2 (June 2015) - Poffenbarger, Hanna J.; Mirsky, Steven B.; Teasdale, John R.; Spargo, John T.; Cavigelli, Michel A.; Kramer, Matthew
Abstract : Crop yields can be similar in organic and conventional systems even when weed biomass is greater in organic systems. Greater weed tolerance in organic systems may be due to differences in management-driven soil fertility properties. The goal of this experiment was to determine whether soil collected from a long-term organic cropping system with a diverse crop rotation and organic fertility inputs would support higher soil nitrogen (N) resource partitioning, as indicated by overyielding of corn–weed mixtures, than a cropping system with a less diverse crop rotation and inorganic N inputs. A replacement series greenhouse experiment was conducted using corn : smooth pigweed and corn : giant foxtail proportions of 0 : 1, 0.25 : 0.75, 0.5 : 0.5, 0.75 : 0.25, and 1 : 0 and harvested at 29, 40, or 48 d after experiment initiation (DAI). The monoculture density of corn was 4 plants pot −1 and the monoculture density of each weed species was 36 plants pot −1 . Corn was consistently more competitive than both weed species at 40 and 48 DAI when soil inorganic N was limiting to growth. Corn–smooth pigweed mixtures had greater shoot biomass and shoot N content than expected based on the shoot biomass and shoot N content of monocultures (i.e., overyielding) at the onset of soil inorganic N limitation, providing some evidence for N resource partitioning. However, soil management effects on overyielding were infrequent and inconsistent among harvest dates and corn–weed mixtures, leading us to conclude that management-driven soil fertility properties did not affect corn–weed N resource partitioning during the early stages of corn growth.